The role of neuro-specific dihydropyrimidinase-related protein 2 (dpyl2) in spatial memory formation in teleosts - D. V. Garina; V. V. Bol’shakov; I. Y. Toropygin; A. A. Mekhtiev; A. M. Andreeva (Regulatory Mechanisms in Biosystems, 2018)
This article presents the results of an experiment on the influence of serotonin-modulating anticonsolidation protein (SMAP) on the spatial memory formation of juvenile goldfish Carassius auratus (L.) in a maze with food reinforcement. Three experimental fish groups were formed: (1) intact animals, (2) experimental group (fish injected ICV with SMAP in 24 h before the beginning of training; 2 μl, 1.5 mg·ml–1), (3) active control group (fish injected ICV with inactivated SMAP). Goldfishes of the experimental group demonstrated the lowest capability for spatial recognition: the maximum level of performance of the task was on 4th day of the training – 38%, while the values of this index in fishes of the control and intact groups were 70% and 63% respectively. In general, throughout the period of the training the average value of task performance was 16% in the SMAP-injected fish (in the control and intact groups – 42% and 53%, respectively). By using Ds-Na-polyacrylamide gel electrophoresis SMAP compositeon has been revealed. It was found that it consists of 10–12 protein components, among which four proteins dominated. They were identified by mass spectrometry MALDI-TOF: spectrin, dihydropyrimidinase-related protein 2 (DPYL2), tubulin and actin. It has been suggested that the most likely candidate responsible for the negative effects of SMAP on fish memory formation is DPYL2. It was hypothesized that anticonsolidation effect of SMAP is caused by the effect of DPYL2 which blocks the growth of axons or its cytostatic activity which leads to disorders in formation of new neurons in the brain as a result of learning.